Bridging the Digital Divide through Korea Cooperation - Arko, A.B.; Owusu, B.A.; Kwadzo, G. (African and Asian Studies, 2019)
The purpose of this paper is review the objectives and functions for which the Ghana-Korea Information Access Center ( IAC ) was set-up at the University of Ghana, Legon in 2012. This type of facility is one of the very few established in Ghana to bridge the digital divide through Ghana-Korea co-operation. Sharing information on its status and development will throw important light on a key Ghana-Korea Project in the Information and Communication Technology ( ICT ) sector, provide critical guidance for the development of future centres and lay the the basis for exploring possibilities for co-operation in ICT between the the two countries. The paper draws its data from interviews (involving users of the IAC ) and documented information on the project. The paper traces the developmental processes (physical, institutional and administrative) for the setting up of the IAC and points up the lessons learnt.
Keywords: Digital divide; Ghana; Information and Communication Technology (ICT); Information centres; Internet; Korea; University of Ghana